2004
DOI: 10.1245/aso.2004.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Recurrence After Breast Cancer in BRCA1/2 Mutation Carriers

Abstract: Breast cancer patients with BRCA1/2 mutations have a similar outcome as non-mutation carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 30 publications
2
25
1
Order By: Relevance
“…In the study of Rebbeck et al (2004) described above, the 105 women who underwent BPM were at risk for 557.36 person-years, giving a rate of onset of BC of 0.0036 per annum, similar to that for the general population shown in Figure 5. Furthermore, there seems to be no significant difference in survival rates after onset between BRCA1/2 mutation carriers and non-carriers (Verhoog et al, 1998(Verhoog et al, , 1999El-Tamer et al, 2004). From Hartmann et al (2001), we deduce an average annual mortality rate from BC of 0.00067 (2 events/2970 person-years) for mutation carriers who underwent BPM, which is also similar to the level in the general population.…”
Section: Treatment For Unaffected Carriers: Bilateral Prophylactic Masupporting
confidence: 56%
“…In the study of Rebbeck et al (2004) described above, the 105 women who underwent BPM were at risk for 557.36 person-years, giving a rate of onset of BC of 0.0036 per annum, similar to that for the general population shown in Figure 5. Furthermore, there seems to be no significant difference in survival rates after onset between BRCA1/2 mutation carriers and non-carriers (Verhoog et al, 1998(Verhoog et al, , 1999El-Tamer et al, 2004). From Hartmann et al (2001), we deduce an average annual mortality rate from BC of 0.00067 (2 events/2970 person-years) for mutation carriers who underwent BPM, which is also similar to the level in the general population.…”
Section: Treatment For Unaffected Carriers: Bilateral Prophylactic Masupporting
confidence: 56%
“…One study on Israeli women concluded that breast cancer specific rates of death are similar between carriers of a BRCA1/2 founder mutation and non-carriers, with the hazard ratio among BRCA1 carriers to be 0.76 and 95% confidence interval (CI) 0.45~1.30, P=0.31; and the hazard ratio among BRCA2 carriers to be 1.3 and 95% CI 0.80~2.15, P=0.28 (Rennert et al, 2007). Another two studies conducted in New York and Rotterdam presented the same negative results that breast cancer specific survival is similar between the mutation carriers and non-carriers in breast cancer patients and patients at high risk for breast cancer, respectively (El-Tamer et al, 2004;Brekelmans et al, 2006).…”
Section: Prognosismentioning
confidence: 88%
“…However, the question of poorer survival is still unresolved today. Some reports have failed to confirm this trend [20][21][22][23][24] (Table 1) and, as discussed by several authors [31][32][33], many of these studies which were not conducted in an outbred population, are subject to potential selection biases, particularly toward survival, i.e. the individual's vital status was not independent of the ascertainment.…”
Section: Introductionmentioning
confidence: 99%